DEVELOPING AN ECOLOGICAL CURRICULUM FOR ENGLISH LANGUAGE LEARNERS - Rustamova Adash Eshankulovna; Musurmonova Saodat Jamshidovna (TADQIQOTLAR, 2025)
Developing an ecological curriculum for English Language Learners (ELLs) involves integrating environmental education with language learning. This approach not only helps students improve their English skills but also raises awareness of ecological issues and fosters a sense of stewardship for the environment. Ecological curriculum goals and objectives includes language proficiency: enhance listening, speaking, reading, and writing skills in English, environmental awareness: foster understanding of key ecological concepts and issues (e.g., biodiversity, climate change, sustainability), cultural connections: explore local ecosystems and cultural perspectives on environmental issues. Within the life domains, the educational team identifies the environments where it is most desirable for the student with severe disabilities to participate. The student’s current home, school, and community environments are considered, and particular attention is placed on integrated or "typical" environments used by peers without disabilities, even if the integrated environments are not currently used by or available to the student. Following are considerations for each environment: